Non-Invasive Monitoring of Intracranial Pulse Wave During Body Tilting Test - Ragauskas, A.; Daubaris, G.; Petkus, V.; Raišutis, R.; Chomskis, R.; Šliteris, R.; Deksnys, V.; Guzaitis, J.; Lengvinas, G.; Rugaitis, A. (Elektronika ir Elektrotechnika, 2008)
Studies have shown that transintracranial time-of-flight (TTF) sonography displays non-invasively and in real-time the relative changes in ultrasound velocity which occur in the intracranial parenchyma and reflects the intracranial pressure (ICP) waveform and mean value trends. In order to investigate the value of such non-invasive ICP monitoring for physiological examination of intracranial dynamics the non-invasive recordings of ICP pulse waves were obtained during body tilting tests of healthy volunteers. It has been shown that consistent changes occur during body tilting in the TTF data. A minimum is seen in the measured by TTF pulse wave amplitude in the low pressure range of the intracranial pressure-volume relationship. However, the transintracranial time-of-flight sonography appears to have the capability of investigating intracerebral parenchyma dynamics in a non-invasive manner. Ill. 3, bibl. 25 (in English; summaries in English, Russian and Lithuanian).